2009
DOI: 10.1080/03235400701390729
|View full text |Cite
|
Sign up to set email alerts
|

Management ofBittergourd yellow mosaic virus(BGYMV) by using virus inhibiting chemical, biocontrol agents, antiviral principles (AVP) and insecticide

Abstract: Bitter gourd Yellow Mosaic Virus (BGYMV) is a Whitefly transmitted geminivirus. BGYMV causes yellow mosaic disease in bitter gourd. This disease attains significance because the virus causing this disease is capable of attacking the crop at all stages. There was a severe yield loss in bitter gourd plants due to the infection of BGYMV. Bitter gourd plants treated with Bougainvillea spectabilis challenge inoculated with BGYMV reduced the disease incidence and increased the plant growth. In the above treatment th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Similar results reported by Chatterjee and Ghosh (2008) in Mestha against yellow vein mosaic disease. Rajinimala et al, (2009) and Anuradha et al, (2015) also discovered similar results in bitter gourd against yellow mosaic virus, in banana against bunchy top virus.…”
Section: Protein Percentagementioning
confidence: 53%
“…Similar results reported by Chatterjee and Ghosh (2008) in Mestha against yellow vein mosaic disease. Rajinimala et al, (2009) and Anuradha et al, (2015) also discovered similar results in bitter gourd against yellow mosaic virus, in banana against bunchy top virus.…”
Section: Protein Percentagementioning
confidence: 53%
“…BGYMV, being a Geminiviridae family member (Begomovirus genus), is a disease-causing virus causing an effect on the loss of yield due to vector whitefly, Bemisia tabaci. To control the disease, initiation of systematic infection resistance method in the bitter gourd crop counter to BGYMV is used (Rajinimala et al 2009). The infection rate has reliably decreased at 45 days after planting DAS by seed treatment with P. fluorescens and P. chlororaphis, and further, it is essentially diminished at 75 DAS contrasted with immunized control plants (untreated) (Rajinimala et al 2009).…”
Section: Bitter Gourd Yellow Mosaic Virus (Bgymv)mentioning
confidence: 99%
“…It is indicated that BS and AS have a positive effect on plant growth. Similarly, bitter gourd plants treated with B. spectabilis (BS) challenge inoculated with bitter gourd yellow mosaic virus (BGYMV) reduced the disease incidence and increased plant growth (Rajinimala et al, 2009). Salicylic acid is known as an inducer of plant defense responses against pathogens.…”
Section: Asmentioning
confidence: 99%
“…The protein's mode action to suppress virus infection in plants is through activation of antiviral by ribosome-inactivating proteins (RIPs) and ISR (Vivanco et al, 1999). Plant extracts able to suppress the infection of viruses such as Cucumber mosaic virus (CMV), Tobacco mosaic virus (TMV), Tomato mosaic virus (ToMV), Tomato spotted wilt virus (TSWV), Potato virus Y (PVY), Potato virus X (PVX), Potato leafroll virus (PLRV), Potato tuber spindle viroid (PSTVd), Cucumber green mottle mosaic virus (CGMMV), Turnip mosaic virus (TuMV), Bitter gourd yellow mosaic virus (BGYMV) and Bean common mosaic virus (BCMV) (Balasarawathi et al, 1998;Balasubrahmanyam et al, 2000;Baranwal & Verma, 1997;Damayanti & Panjaitan, 2014;Deepthi et al, 2007;Gholizadeh et al, 2004;Hersanti, 2004;Kubo et al, 1990;Kumalasari et al, 2015;Kurnianingsih & Damayanti, 2012;Madhusudhan et al, 2011;Rajinimala et al, 2009;Sharma et al, 2007). The effectiveness of plant extracts to suppress the virus infection is depends on the virus species.…”
Section: Introductionmentioning
confidence: 99%